2011
DOI: 10.1007/s12374-011-9180-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Hormone and Stress-Induced Expression of FaRE1 Retrotransposon Promoter in Strawberry

Abstract: Retrotransposons are the most abundant mobile elements in the plant genome and seem to play an important role in genome reorganization induced by environmental challenges. Their success in this function depends on the ability of their promoters to regulate plant adaptation to biotic and abiotic stresses. In this study, the promoter region of FaRE1 was amplified in the strawberry genome, and promoter::GUS fusion was constructed. We produced transgenic strawberry plants carrying FaRE1 promoter:: GUS-fusion genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…The low transcript abundance of LTR-REs in plants has often been reported [51,[53][54][55][56]. In certain species, increased expression in plants exposed to biotic or abiotic stresses was reported; however, the global level of expression remained low even during stressful treatments [57][58][59][60][61][62]. Our data indicated that 21/180 sequences were barely expressed and only three sequences were transcribed at levels comparable to those of the majority of actin-and tubulin-encoding reference genes.…”
Section: Discussionsupporting
confidence: 55%
“…The low transcript abundance of LTR-REs in plants has often been reported [51,[53][54][55][56]. In certain species, increased expression in plants exposed to biotic or abiotic stresses was reported; however, the global level of expression remained low even during stressful treatments [57][58][59][60][61][62]. Our data indicated that 21/180 sequences were barely expressed and only three sequences were transcribed at levels comparable to those of the majority of actin-and tubulin-encoding reference genes.…”
Section: Discussionsupporting
confidence: 55%
“…As a matter of fact, only three elements were more expressed than an actinencoding gene in control roots and only two in roots of treated plants. In some cases, LTR-REs have been shown to be activated at transcriptional and possibly transpositional level by different treatments mimicking abiotic and biotic stresses (Kashkush et al 2003;Liu et al 2004;He et al 2012;Ito et al 2013;Voronova et al 2014). For example, transcription of LTR-REs of both Copia and Gypsy superfamilies were induced by gibberellin and salicylic acid in cotton and pine (Hawkins et al 2008;Fan et al 2014); ABA, cytokinins and auxins induced strawberry FaRE1 (He et al 2010); tissue culture, jasmonate and fungal elicitors activated Tto1 in tobacco (Takeda et al 1999;Liu et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Some TEs such as Bare1 and FaRE1 in plants respond to Abscisic Acid (ABA), a hormone associated with stress response. (46,47) This was elegantly shown by fusing a GUS protein to FaRE1 and monitoring GUS signal after administration of ABA. (47) Stress-responsive elements are diverse and common among TEs, it is hypothesized that they confer a competitive advantage against TEs lacking responsive elements in terms of transposition rate.…”
Section: Tes With Stress Responsive Elementsmentioning
confidence: 99%